2020
DOI: 10.1038/s42255-020-0175-z
|View full text |Cite
|
Sign up to set email alerts
|

PTH hypersecretion triggered by a GABAB1 and Ca2+-sensing receptor heterocomplex in hyperparathyroidism

Abstract: Molecular mechanisms mediating tonic secretion of parathyroid hormone (PTH) in response to hypocalcemia and hyperparathyroidism (HPT) are unclear. Here we demonstrate increased heterocomplex formation between the calcium-sensing receptor (CaSR) and metabotropic GABA B1 receptor (GABA B1 R) in hyperplastic parathyroid glands (PTGs) of patients with primary and secondary HPT. Targeted ablation of GABA B1 R or glutamic acid decarboxylase 1 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 43 publications
(67 reference statements)
0
32
0
Order By: Relevance
“…Future studies will be required to find out how these oligomers can be stabilized, as upon detergent solubilization, most of the receptors regress to their dimeric state. Another interesting avenue are heterodimers between different types of receptors, such as GB1 and CaSR, which have been described recently ( 120 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will be required to find out how these oligomers can be stabilized, as upon detergent solubilization, most of the receptors regress to their dimeric state. Another interesting avenue are heterodimers between different types of receptors, such as GB1 and CaSR, which have been described recently ( 120 ).…”
Section: Discussionmentioning
confidence: 99%
“…It maintains Ca 2+ homeostasis by the modulation of parathyroid hormone (PTH) secretion from parathyroid cells and the regulation of Ca 2+ reabsorption by the kidney ( Brown, 2013 ). Recently, it has been reported that CaSR is also a phosphate sensor that can sense moderate changes in extracellular phosphate concentration ( Centeno et al, 2019 ; Chang et al, 2020 ; Geng et al, 2016 ). Dysfunctions of CaSR or mutations in its genes may lead to Ca 2+ homeostatic disorders, such as familial hypocalciuric hypercalcemia, neonatal severe hyperparathyroidism, and autosomal dominant hypocalcemia ( Hendy et al, 2009 ; Pollak et al, 1993 ; Ward et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Insights into the activation mechanism of class C GPCRs begin to emerge. Class C GPCRs exist as obligate homo-or heteromers and regulate major biological functions as diverse as mineral and skeletal metabolism (82) and neurological function (83). Earlier structural studies of isolated ECDs of several class C GPCRs demonstrated that agonist binding induces the closure of the VFT (Venus flytrap) domain of their ECDs, leading to rearrangement of the interface between the dimer ECDs and bringing them into close proximity-a hallmark of class C GPCR activation (84)(85)(86)(87)(88).…”
Section: Structural Insights Into Gpcr Activationmentioning
confidence: 99%